The Effectiveness of the Self-Organized Learning Environment (SOLE) Model in Enhancing Students’ Learning Activeness in Fiqh Learning - Alvia Damayanti; Wan Jamaluddin; Uswatun Hasanah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the impact of the Self-Organized Learning Environment (SOLE) model on students’ learning activeness in Fiqh at MTs Al-Ma’ruf Margodadi. The research emerged from classroom conditions that were largely teacher-centered, with limited technology integration and minimal student participation in discussion and problem-solving. A quasi-experimental design was employed, involving class VIII.B as the control group and VIII.A as the experimental group applying SOLE. Data were collected using a learning activeness questionnaire covering five indicators; 20 items were declared valid, with a reliability coefficient of α = 0.607. This coefficient meets the minimum 0.60 standard considered acceptable by several researchers in social science studies, particularly for context-based instruments. The findings indicate that SOLE significantly enhances students’ participation, especially in questioning, discussion, and problem-solving activities, demonstrating its potential as an effective approach in Islamic Education to cultivate more independent and engaged learners.